Rediscovery of Chinommatia littoralis (Tesch, 1918) (Crustacea: Decapoda: Brachyura: Chasmocarcinidae) from Tanimbar Island, Indonesia - Ng, Peter K. L.; Rahayu, Dwi Listyo (Zootaxa, 2017)
The male of Chinommatia littoralis (Tesch, 1918) is described for the first time based on material from Tanimbar Island, Indonesia. The structure of the male first and second gonopods are distinct and more closely resemble those of Notopelta mortenseni (Serène, 1964), but the species is retained in Chinommatia Ng & Castro, 2016, because of the structure of its carapace, cheliped, and thoracic sternum. Specimens reported as C. littoralis from Vietnam by Zarenkov (1972) and South China Sea by Chen (1998) are in fact C. cavimanus (Rathbun 1914). Zarenkov’s (1972) record of Chinommatia cavimanus from Vietnam belongs to Chasmocarcinops gelasimoides Alcock, 1900, instead.